Uma introdução ao operador phi-Laplaciano - Silva, Victor Vinicius França (2020)
In this work we will study the existence of weak solutions in an Orlicz-Sobolev space of the Dirichlet's problem of the [formula]. Where [formula] is a bounded domain in [formula]. If the function [formula] satisfies some technical conditions and [formula] obeys some conditions of subcriticality and superlinearity with respect to the function [formula], we obtain the existence of nontrivial solutions which are of mountain pass type.